Correlation of self-esteem with oral hygiene behaviour and oral health status among adult dental patients - Billa, A. L.; Sukhabogi, J. R.; Doshi, D.; Jummala, S.; Turaga, S. S. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Self-esteem is a psychological construct that has been consistently linked to general and oral health. However, most studies interpolating self-esteem and oral health behaviour have been focused on children and adolescents, and there is a dearth of scientific literature on adults. Hence, this study, that is aimed to correlate self-esteem with oral hygiene behaviour and oral health status in Telugu-speaking adult dental patients. Methods. A cross-sectional study involving adult dental patients who were 35–44 years of age and visited the Government Dental Hospital in Hyderabad city, India, was conducted. Self-esteem was assessed using the Telugu-translated version of the Rosenberg Self-esteem Scale, oral health behaviour was determined using the Oral Hygiene Behaviour Index and oral health assessment was performed using the World Health Organization Dentition status, the modified Community Periodontal Index and the Loss of Attachment. Results. A total of 456 patients were included in this study. Most of the participants reported low selfesteem, with a mean score of 11.8 ± 2.7. Patients with primary school education reported higher self-esteem scores than those with high school and university education (p = 0.0001). Furthermore, low Oral Hygiene Behaviour Index scores (64.9%) in the study population and high Decayed, Missing, Filled Teeth scores in females (5.7 ± 4.4; p = 0.09) were noted. None of the variables (Decayed, Missing, Filled Teeth scores, Oral Hygiene Behaviour, gingival bleeding and Loss of Attachment) were significantly correlated with selfesteem. Multivariable regression analysis revealed that younger age, lower educational level and presence of dental caries resulted in higher odds for high self-esteem (p < 0.01). Conclusion. The findings indicated a significant association between self-esteem and oral health. Individuals with dental caries had significantly higher odds for high self-esteem. Thus, this study emphasises the relevance of psychosocial factors, such as self-esteem, as the mediator of oral health.